2005
DOI: 10.1016/j.indmarman.2004.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Experience as a moderator of involvement and satisfaction on brand loyalty in a business-to-business setting 02-314R

Abstract: This paper examines the relative influence of two key antecedents of brand loyalty-satisfaction and involvement and the moderating role of experience, using a sample of business buyers. The central argument of this paper is that the strength of the effect of these variables on attitudinal brand loyalty will vary with the level of customer experience with purchasing the service. Building on previous research which examined low-risk, customer product settings [Kim, J., Lim, J.S., & Bhargava, M. (1998). The role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(170 citation statements)
references
References 52 publications
(79 reference statements)
5
160
0
5
Order By: Relevance
“…Many companies, instead, search for their ideal partners for co-branding alliances from among their more loyal buyers, but as the current research demonstrates, loyalty is not a predictor of how buyers will perceive the value of a co-branding alliance. Specifying the type of value provided by ingredient brand loyalty to buyers, our paper enhances the knowledge offered by previous industrial marketing studies that found a positive relationship between brand loyalty and a general quality and value created by inter-firm relationships (Bennett, Härtel, & McColl-Kennedy, 2005;Cretu & Brodie, 2007;Kim & Hyun, 2011;Leischnig & Enke, 2011;Michell et al, 2001;Van Riel et al, 2005).…”
Section: Discussionsupporting
confidence: 58%
“…Many companies, instead, search for their ideal partners for co-branding alliances from among their more loyal buyers, but as the current research demonstrates, loyalty is not a predictor of how buyers will perceive the value of a co-branding alliance. Specifying the type of value provided by ingredient brand loyalty to buyers, our paper enhances the knowledge offered by previous industrial marketing studies that found a positive relationship between brand loyalty and a general quality and value created by inter-firm relationships (Bennett, Härtel, & McColl-Kennedy, 2005;Cretu & Brodie, 2007;Kim & Hyun, 2011;Leischnig & Enke, 2011;Michell et al, 2001;Van Riel et al, 2005).…”
Section: Discussionsupporting
confidence: 58%
“…We posit, in the present study, that length of employment and prior business experience specific to the institution involved may be instrumental in ensuring the success of guanxi as a conflict management tool due to the increased knowledge and access to network resources, such as the relationship to advisors and key decision makers and leaders within the firm (Bennett, Härtel, & McColl-Kennedya, 2005). Employees with better institutional knowledge and experience are more able to handle the peculiarities of guanxi in a more nuanced manner that fits each complex situation.…”
Section: Moderating Role Of Length Of Employmentmentioning
confidence: 95%
“…Product information plays a critical role in purchasing decision in e-stores. Information and knowledge about the product are positively related to customer satisfaction [51]. H 4 = A product information is positively related to customer satisfaction on re-purchase intention in e-stores.…”
Section: Product Informationmentioning
confidence: 95%